A clinical study of management of proximal humeral fractures in adults - Khan, Shakil Mohamad; Sheikh, Shifa; Saheb, Shaik Hussain (International Journal of Research in Medical Sciences, 2017)
Background:Fractures of the proximal humerus are one of the commonest fractures encountered by an orthopaedician. The incidence of this fracture has significantly increased perhaps due to the increased vehicular traffic and mechanized life. The approach towards the management of these fractures types of fractures has changed during the course of period. Since the appropriate treatment and results associated with each modality of treatment for these fractures is not defined this study was undertaken. Methods: This longitudinal study was done on 150 cases of proximal humerus fractures which were managed by both conservative and surgically. Initial preoperative clinical and radiological assessment was done and appropriate mode of treatment of given depending upon type of fracture according Neer’s classification. Follow up of patient was done both clinically and radiologically at 2nd, 6th and 8th weeks and assessed for any complications. Final assessment was done according to Neer`s shoulder scoring criteria. Results:The 90 cases were treated conservatively and 60 surgically. Maximum follow up was 9 months and minimum 4 month with an average follow- up of 6.67 months. Our series showed excellent result in 70 cases (46.6%), satisfactory in 65 cases (43.3%) and fair in 15 cases (10%). Conclusion:Undisplaced fractures of the proximal humerus can be managed conservatively and non-displaced tuberosity fractures, if managed conservatively, give good results. Displaced two or three part fractures in young patients need anatomical reduction with internal fixation. Conservative treatment of four part fractures, four part fracture dislocation and anatomical neck fractures gives poor results and so primary hemiarthroplasty is indicated. There is direct relationship between displaced proximal humeral fractures between fracture severity i.e. greater displacement, communition, and crushing and the eventual results that is more than the initial insult, worse the prognosis. Rehabilitation is the key to success.